(untitled) (Global Journal of Management and Business Research, 2016)
The paper will be aimed at addressing the analysis of value chain of Sudan Dairy industry. Sudan has been facing plenty of challenges in terms of their dairy industry, it being the core earning source for their people. This importance is evident in the quantity and representation of value chain components represented by producers and industry that they are specific, without considering the distributors. The integration of markets and governmental support for the country would create an increasing standardization of demands consumers, the spread of productive activity around the world. The systematic transition in the dairy industry would begin to develop international strategies focusing on the specifics of different regions in which they operate. Therefore, a better and improved value chain procedure would positively complement the Sudan dairy industry, endowing their people with better employment opportunities too. The research approach used in the paper is based on secondary qualitative design. This approach enabled the researcher to extract relevant information regarding the topic, efficiently.